Health service approaches to providing care for people who seek treatment for obesity: identifying challenges and ways forward - Michelle Gooey; Catherine A Bacus; Divya Ramachandran; Milan K Piya; Louise A Baur (Public Health Research & Practice, 2022)
Objective: This paper aims to identify challenges in current health service approaches to providing optimal care for people who seek treatment for obesity.